2014
DOI: 10.1186/s12870-014-0376-2
|View full text |Cite
|
Sign up to set email alerts
|

Allelic diversity in the transcriptomes of contrasting rust-infected genotypes of Lathyrus sativus, a lasting resource for smart breeding

Abstract: BackgroundGrass pea (Lathyrus sativus L.) is a valuable resource for potentially durable partial resistance to rust. To gain insight into the resistance mechanism and identify potential resistance genes, we generated the first comprehensive transcriptome assemblies from control and Uromyces pisi inoculated leafs of a susceptible and a partially rust-resistant grass pea genotype by RNA-seq.Results134,914 contigs, shared by both libraries, were used to analyse their differential expression in response to rust in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 87 publications
0
55
0
Order By: Relevance
“…In addition, expression analysis using RNA-sequencing was also employed in grass pea to tackle the molecular mechanisms underlying prehaustorial rust resistance (Almeida et al 2014b). These authors identified several pathogenesis-related proteins as possibly involved in grass pea resistance to rust, that included some regulated by the well-studied mildew resistance locus O (MLO) gene.…”
Section: Integration Of New Biotechnologies In Breeding Programmesmentioning
confidence: 99%
“…In addition, expression analysis using RNA-sequencing was also employed in grass pea to tackle the molecular mechanisms underlying prehaustorial rust resistance (Almeida et al 2014b). These authors identified several pathogenesis-related proteins as possibly involved in grass pea resistance to rust, that included some regulated by the well-studied mildew resistance locus O (MLO) gene.…”
Section: Integration Of New Biotechnologies In Breeding Programmesmentioning
confidence: 99%
“…A clade V MLO gene, from pepper, CaMLO2 , has also been associated with susceptibility to bacterial and oomycete pathogens, and to drought 19 20 . In addition, the expression of some Lathyrus sativus MLO transcripts were induced shortly after rust infection in resistant genotypes, which might suggest their involvement in rust resistance 21 . Although the exact role of clade V MLOs is still unclear, they might interfere with the plant immune response to stresses.…”
mentioning
confidence: 96%
“…Of these 205,691 tags were derived from L. sativus inoculated with A. lathyri and 193,957 tags from control plants. These tags corresponded to 14,386 unique sequences (UniTags) of which 13,773 (95.7%) were successfully annotated to the L. sativus reference dataset (Almeida et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…A multi-step BLAST procedure was used to annotate the UniTag reads to ensure an unambiguous assignment to their corresponding transcript and to eliminate any remaining adaptor sequences. Reference datasets were generated by own de-novo-assembly (Almeida et al, 2014 ) and downloaded from the publicly accessible Fabaceae databases using the nucleotide database from the National Center for Biotechnology Information (NCBI). UniTag reads were successively aligned against these reference datasets in the following order: (1) 26 bp de-novo-assembly dataset with a minimum BLAST-score of 42; (2) UniTags which did not attain the specified BLAST score in the previous step were aligned against the complete NCBI dataset with the same required BLAST score of 42 or above.…”
Section: Methodsmentioning
confidence: 99%